1994
DOI: 10.1016/0304-3959(94)90188-0
|View full text |Cite
|
Sign up to set email alerts
|

Pain prevalence, severity and impact in a clinic sample of multiple sclerosis patients

Abstract: Previous studies have reported variable prevalence of pain in multiple sclerosis (MS) and have not documented the impact of pain on daily living. In this consecutive series, we report on data collected from structured interviews with 85 patients seen within a 16-month period at a regional referral clinic. The prevalence of pain for the month preceding assessment was 53%. There were no significant differences between patients who did and those who did not report pain on the basis of patient demographics (age, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
151
3
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(174 citation statements)
references
References 12 publications
19
151
3
1
Order By: Relevance
“…More than half of our patients endorsed multiple nocturnal symptoms. While numerous studies have identified pain as a predictor of poor sleep quality, fatigue, and overall diminished functioning in MS patients, 39,40 our findings underscore the point that nocturnal discomfort experienced by MS patients may be described in terms other than pain. More importantly, our data highlight the importance of addressing treatable symptoms that may cause fatigue in patients with MS through reduced sleep efficiency or other mechanisms.…”
Section: Discussionsupporting
confidence: 56%
“…More than half of our patients endorsed multiple nocturnal symptoms. While numerous studies have identified pain as a predictor of poor sleep quality, fatigue, and overall diminished functioning in MS patients, 39,40 our findings underscore the point that nocturnal discomfort experienced by MS patients may be described in terms other than pain. More importantly, our data highlight the importance of addressing treatable symptoms that may cause fatigue in patients with MS through reduced sleep efficiency or other mechanisms.…”
Section: Discussionsupporting
confidence: 56%
“…Some previous studies have reported that MS-related disability is associated with pain, 3,6 whereas others have found no association. 34,35 Possible explanations for conflicting findings include vast differences in sample sizes (with larger, survey studies more likely to find significant associations), different aspects of pain explored (acute pain, chronic pain, experience of any pain, frequency, intensity, or pain interference), different instruments used to measure different aspects of pain, and differences in how MS-related disability is measured (clinical examination or self-report). Thus, the relationship between pain and disability remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Archibald and colleagues 99 found no difference between the pain and no-pain groups in the Kurtze EDSS, but did find that those with pain had a significantly lower score on the Mental Health Inventory (MHI) (mean 159.2, SD. 28.4, versus mean 170.4, SD.…”
Section: Prevalencementioning
confidence: 99%